How would you solve this for c?

6 - (2c + 5) = 12

6 - (2c + 5) = 12

6 - (2c + 5) = 12

6 - 2c - 5 = 12 {took out parentheses, used distributive property with negative sign}

-2c + 1 = 12 {combined like terms}

-2c = 11 {subtracted 1 from both sides}

c = -11/2 {divided both sides by -2}

- Algebra House

6 - 2c - 5 = 12 {took out parentheses, used distributive property with negative sign}

-2c + 1 = 12 {combined like terms}

-2c = 11 {subtracted 1 from both sides}

c = -11/2 {divided both sides by -2}

- Algebra House